PERANCANGAN ULANG TATA LETAK GUDANG DISTRIBUTOR BAN PADA PT XTC - Lumban Toruan, Lionel Richie; Elsya Paskaria Loyda Tarigan (Computer Science and Industrial Engineering, 2024)
The rapid development of global industries and technology has complicated the layout of warehouse facilities in manufacturing. PT XTC, a major tire distributor in Indonesia, faces inefficiencies in its warehouse layout, causing cross movements, poor space utilization, and difficulties for forklift operators. This study aims to redesign the tire layout in PT XTC’s distribution warehouse using the class-based storage method, which groups materials based on popularity to enhance efficiency and productivity. The study employs direct observation, interviews, and literature reviews, collecting data on tire quantities, material inflows, and outflows from October 2023 to March 2024. Data analysis includes calculating the frequency of material movements, classifying materials into fast-moving, medium-moving, and slow-moving categories, and measuring penangan material distances and costs in both the initial and proposed layouts. Results show that the class-based storage method groups materials into class A (67.4%), class B (18.3%), and class C (8.3%). The initial layout shows a material movement distance of 3,514,000 meters and handling costs of Rp.509,530,000, while the redesigned layout reduces these figures to 1,045,800 meters and Rp.151,641,000, respectively. The redesign provides a more efficient space and lower handling costs.